CLASSICAL NIGHT: SEBUAH SAJIAN MUSIK KLASIK OLEH KOMUNITAS HIMASIKSTRING - Likhamelia, Istiso; Susetyo, Bagus (Jurnal Seni Musik, 2019)
Classical music is not necessarily acceptable to all levels of society. Nevertheless, the Himasikstring Community of Yogyakarta State University has consistently been able to hold concerts with classic themes. One of the goals of this community is to introduce classical music to the community. The formulation of the problem in this research is how is the profile of the Himasikstring community and how is the presentation of Classical Night concerts at Yogyakarta State University in 2018. The research method used in the research is qualitative descriptive method. Data collection techniques used by researchers include, namely, literature studies, observation, interviews, and document studies. Based on the results of the study, it can be concluded that Himasikstring actively held classical music concerts and introduced classical music to the public since 2012, and Classical Night concerts consisted of elements of composition and presentation elements.